Cover Picture: Small‐Molecular‐Weight Additives Modulate Calcification by Interacting with Prenucleation Clusters on the Molecular Level (Angew. Chem. Int. Ed. 40/2022). Issue 40 (31st August 2022) - Duchstein, Patrick; Schodder, Philipp I.; Leupold, Simon; Dao, Thi Q. N.; Kababya, Shifi; Cicconi, Maria R.; de Ligny, Dominique; Pipich, Vitaliy; Eike, David; Schmidt, Asher; Zahn, Dirk; Wolf, Stephan E.
Abstract : Amorphous calcium carbonate (ACC) is a pivotal precursor in biomineralization, central to geological and industrial calcification. Some small organic molecules have the ability to affect ACC formation, composition, and stability powerfully. In their Research Article (e202208475 ), Asher Schmidt, Dirk Zahn, Stephan E. Wolf et al. decode the underlying molecular mechanisms that regulate both prenucleation cluster and solution composition and proceed outside the established conceptional framework.